Effects of tree species identity on soil microbial communities in Juglans nigra and Quercus rubra plantations - Frene, Juan P.; Lawson, Shaneka S.; Lue Sue, Niall D.; Crawford, Ralph H.; Gardner, Terrence G. (Frontiers in Microbiology, 2024)
Understanding how different tree species affect soil microbial communities is crucial for sustainable forestry and ecosystem management practices. Despite Black walnut (Juglans nigra L.) forestry having a rich history, the overall comprehension of how this hardwood species influences soil remains incomplete.In earlier studies, we examined the effects of hardwood plantations on soil chemical properties and their interaction with microbial biomass, however, we highlight the importance of studying the soil microbial communities and their relationship with soil properties in greater depth. Building on this foundation, our research focused on evaluating microbiome compositions beneath J. nigra and another hardwood, Northern red oak (Quercus rubra L.) after a decade of establishment. We uncovered intriguing patterns within the soil bacterial/archaeal and fungal structures by conducting meticulous analyses utilizing amplicon sequencing alongside soil chemical properties. Our findings underscore that tree species play a pivotal role in shaping soil microbial structures, a role that surpasses even seasonal and depth influences.Most notably, J. nigra stands out for its ability to enhance microbial diversity, as evidenced by increased alpha-diversity indices compared to baseline values. Conversely, Q. rubra tends to decrease these indices.Significant disparities in microbial composition between the two tree species were evident, with J. nigra exhibiting enrichment in certain taxa such as Nitrospira, Geobacter, and Bacillus while Q. rubra showed enrichment in others like Acidobacteriota and ectomycorrhizal fungi. Furthermore, we also observed differences in co-occurrence networks by delving deeper into the interconnections within the soil microbiota. In both fungal and bacterial/archaeal communities, J. nigra and Q. rubra notably decreased the number of connections within their networks, while Q. rubra increased some, suggesting a more interconnected network. These differences were further highlighted by network metrics with Q. rubra displaying a higher mean degree and clustering coefficient. Additionally, our analysis revealed that tree species influence soil chemical properties, either directly or indirectly, thereby affecting soil bacterial and fungal communities. In conclusion, our study elucidates the intricate interplay between tree species and soil microbiota, emphasizing the need to consider these relationships in forestry and ecosystem management practices.